Intervention to Enhance Successful Aging: Literature Review for the Eldery - Mumtaz Afridah (Prophetic : Professional, Empathy, Islamic Counseling Journal, 2025)
This research aims to analyze the appropriate interventions to increase successful aging in the elderly and the factors that affect it. Successful aging is a concept that includes physical, mental, and social well-being of the elderly. At this time there is a gap between increasing the life expectancy of the elderly and the happiness and welfare of the elderly. This shows the need for a comprehensive treatment for the elderly as a reference for the treatment of the elderly in filling their old age. The research method used is a qualitative method with literature study. Literature study is research that has a role to outline the main concepts and relevant previous findings, as well as to identify the development of research in a topic. The research results show that there are various interventions based on factors that can affect successful aging, including social dimension factors, physical dimension factors, psychological dimension factors, spiritual dimension factors.